2015
DOI: 10.1093/aobpla/plv121
|View full text |Cite
|
Sign up to set email alerts
|

Performance of hybrid progeny formed between genetically modified herbicide-tolerant soybean and its wild ancestor

Abstract: Gene flow may occur between genetically modified (GM) crops and wild relatives and the fate of escaped transgenes depends on the performance of hybrids and the fitness of the transgene. Hybrids were formed by hand-crossing a GM strain of glyphosate-tolerant soybean and its non-GM counterpart with wild soybean and were assessed in this study. The hundred-seed weight of hybrids was significantly higher than that of wild soybean. However, no overall difference in plant growth was found between GM and non-GM hybri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
20
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 37 publications
5
20
1
Order By: Relevance
“…Traits like fast growth rate, self-compatibility (crop traits) could favor weediness [32]. A gain of herbicide-resistance gene through hybridization with GM plants could lead toward its persistence in the agricultural habitat [33]. There exists a contradiction among scientists about the establishment of transgene recipients as weeds in the environment.…”
Section: Superweedinessmentioning
confidence: 99%
See 1 more Smart Citation
“…Traits like fast growth rate, self-compatibility (crop traits) could favor weediness [32]. A gain of herbicide-resistance gene through hybridization with GM plants could lead toward its persistence in the agricultural habitat [33]. There exists a contradiction among scientists about the establishment of transgene recipients as weeds in the environment.…”
Section: Superweedinessmentioning
confidence: 99%
“…Based on the risk of increased fitness, certain traits are strong candidates which can enhance chances of competitiveness, such as tolerance to herbicides, resistance to various stress, pathogens and pests, and traits responsible for enhanced growth [34]. Plants can develop several herbicide-resistance mechanisms, such as herbicide detoxification, changes in the intracellular compartmentation of herbicides, target site insensitivity, reduced herbicide entry, reduced herbicide translocation, and target site overproduction [33].…”
Section: Superweedinessmentioning
confidence: 99%
“…Besides the initial crop–weed hybridization, the likelihood of transgenes or other alleles spreading from crops to related wild populations depends on the fitness of the first and successive generations of hybrids (Hauser et al 1998 ; Gueritaine et al 2002 ; Jenczewski et al 2003 ; Lu and Snow 2005 ; Kuroda et al 2006 ; Guan et al 2015 ; Kan et al 2015 ). Fitness is reflected by vegetative and reproductive growth indicators and determines whether the hybrids can survive and establish (Warwick et al 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…There is a dearth of previous research on the fitness of F1 hybrids obtained from wild and cultivated soybeans, including transgenic soybeans. Guan et al ( 2015 ) measured the F1 hybrids of two wild soybeans and glyphosate-resistant soybean (AG5601) in a greenhouse, and found that two F1 hybrids had similar aboveground biomass, the same or 36% fewer pods, and the same or 54% fewer seeds per plant compared with their wild relatives. However, the 100-seed weight of two F1 hybrids was three times that of their respective wild relatives.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the risk of increased fitness, certain traits are strong candidates which can enhance chances of competitiveness, such as tolerance to herbicides, resistance to various stress, pathogens and pests and traits responsible for enhanced growth(Yang et al, 2012). Plants can develop several herbicide-resistance mechanisms, such as herbicide detoxification, changes in the intracellular compartmentation of herbicides, target site insensitivity, reduced herbicide entry, reduced herbicide translocation and target site overproduction(Guan et al, 2015). The risk of pervasiveness or invasiveness is regarded relatively low, there are some possible biological changes that could lead to weediness such as tolerance to extreme regimes of temperature, water and soil salinity, modification in seed propagation and dormancy characteristics and introduction of resistance to pest or pathogens (Tappeser et al, 2014).…”
mentioning
confidence: 99%